2011
DOI: 10.1158/1538-7445.am2011-2023
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2023: Isolation of breast tumor initiating cells (TICs) by exogenous delivery of the OCT4 transcription factor

Abstract: Tumor initiating cells (TICs) are being extensively studied for their role in tumor etiology, maintenance and resistance to treatment. We describe a novel approach to generate TICs by transduction of human primary breast cell preparations with exogenous expression of the OCT4 transcription factor. The OCT4 transduced breast colonies (OTBCs) underwent an immortalization process, as reflected by loss of p16 and enhanced telomerase expression. OTBCs exhibited cancer stem cell antigens, such as CD44high/CD24low/‐.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…Previous findings have identified that Oct4 and Sox2 are important in the regene ration of many CSCs (20)(21)(22). RT-PCR and IFS assays were used to validate the expression of Oct4 and Sox2 in the A549 spheres.…”
Section: Sphere Cells Express High Levels Of Oct4 Sox2 and Cd133mentioning
confidence: 99%
“…Previous findings have identified that Oct4 and Sox2 are important in the regene ration of many CSCs (20)(21)(22). RT-PCR and IFS assays were used to validate the expression of Oct4 and Sox2 in the A549 spheres.…”
Section: Sphere Cells Express High Levels Of Oct4 Sox2 and Cd133mentioning
confidence: 99%
“…reprogram adult somatic cells into iPSCs (i.e., OCT4, SOX2, KLF4 and c-MYC) to support their tumor initiation capacity. [62][63][64][65] For instance, endogenous expression of the transcription factor OCT4-a master gene playing a pivotal role in the self-renewal and pluripotency of stem cells-in normal breast tissues has been found to induce aberrant self-renewal and expansion of undifferentiated early stem/ progenitor population. 62,63 Similarly to its functioning during somatic reprogramming to stemness, OCT4 overexpression in normal breast tissue results in an activation of self-renewal TFs that is concomitant with the repression of tumor suppressor genes, thus allowing cells to immortalize and gain SC-like features.…”
Section: Low-glucose Tumor Environmentmentioning
confidence: 99%
“…Exogenous expression of Oct4 in human primary breast cells results in transformation of cells with overexpressed telomerase and down-regulated p16. Further injection of these transformed cells in nude mice generated breast carcinomas with metastatic potential [31]. In another recent study, co-expression of both Oct4/Nanog enhanced malignancy in lung adenocarcinoma and induces epithelial-mesenchymal transition (EMT).…”
Section: Can We Reprogram Human Primary Cancer Cells? -The Big Paradoxmentioning
confidence: 99%